2021
DOI: 10.3389/fmolb.2021.719982
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mast Cell-Based Molecular Subtypes and a Predictive Signature in Clear Cell Renal Cell Carcinoma

Abstract: Background: Kidney renal clear cell carcinoma (KIRC) is a common malignant tumor of the urinary system. Surgery is the preferred treatment option; however, the rate of distant metastasis is high. Mast cells in the tumor microenvironment promote or inhibit tumorigenesis depending on the cancer type; however, their role in KIRC is not well-established. Here, we used a bioinformatics approach to evaluate the roles of mast cells in KIRC.Methods: To quantify mast cell abundance based on gene sets, a single-sample g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…However, studies on MCs and the prognosis of different cancers have reached different conclusions. [23][24][25] Similarly, previous studies also observed the anti-and pro-tumor effects of MCs in CC. [13][14][15][16][17] Our study aimed to explore and clarify this question.…”
Section: Discussionsupporting
confidence: 54%
“…However, studies on MCs and the prognosis of different cancers have reached different conclusions. [23][24][25] Similarly, previous studies also observed the anti-and pro-tumor effects of MCs in CC. [13][14][15][16][17] Our study aimed to explore and clarify this question.…”
Section: Discussionsupporting
confidence: 54%
“…As one of the most prevalent primary malignant tumors of the urinary system, KIRC has the characteristics of high heterogeneity, poor prognosis, and distant metastasis ( 4 , 31 , 32 ). It is critical to explore the potential predictor for KIRC treatment and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Using R software's “survival”, “survminer”, and “timeROC' packages, our TRPP was compared to seven other prognostic signatures (a mast cell-based signature developed by Liu et al [ 14 ], an m5C-related risk signature developed by Wu et al [ 15 ], and a four hypoxia-associated long non-coding RNA signature developed by Chen et al [ 16 ], an m6A-lncRNAs prognostic index developed by Lin et al [ 17 ], an autophagy-associated gene prognostic model developed by Wang et al [ 18 ], a nine-RNA binding protein signature developed by Zhong et al [ 19 ], and an inflammasome-related signature developed by Zheng et al [ 20 ]) on the basis of each gene combination in each signature.…”
Section: Methodsmentioning
confidence: 99%